2015
DOI: 10.1007/s12041-015-0477-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of CYP2C19 in a Mexican population: contribution to the knowledge of the inheritance pattern of CYP2C19*17 to develop the ultrarapid metabolizer phenotype

Abstract: CYP2C19 is a polymorphic enzyme that metabolizes a wide variety of therapeutic drugs that has been associated with altered enzymatic activity and adverse drug reactions. Differences in allele frequencies of the CYP2C19 gene have been detected in populations worldwide. Thus, we analysed the alleles CYP2C19*2, CYP2C19*3, CYP2C19*4 and CYP2C19*5 related to the poor metabolizer (PM) phenotype in a Mexican population sample (n = 238), as well as CYP2C19*17, unique allele related to ultrarapid metabolizer phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
2
6
2
1
Order By: Relevance
“…[29][30][31][32] In both our patient and volunteer MM samples, we observed a predominance of the wild-type CYP2C19*1 allele, a low frequency of CYP2C19*2 and an absence of CYP2C19*3 allele, as it has been previously reported. [33][34][35][36][37][38] The frequency of CYP2C19*17 allele found in the present study (MM from Central Mexico) shows a minor nonsignificant difference from that found in a recent report in MM from the state of Jalisco (0.09 and 0.14, respectively). 38 The frequency of ABCB1 3435C4T in the MM population studied here is similar to that found in previous reports.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…[29][30][31][32] In both our patient and volunteer MM samples, we observed a predominance of the wild-type CYP2C19*1 allele, a low frequency of CYP2C19*2 and an absence of CYP2C19*3 allele, as it has been previously reported. [33][34][35][36][37][38] The frequency of CYP2C19*17 allele found in the present study (MM from Central Mexico) shows a minor nonsignificant difference from that found in a recent report in MM from the state of Jalisco (0.09 and 0.14, respectively). 38 The frequency of ABCB1 3435C4T in the MM population studied here is similar to that found in previous reports.…”
Section: Discussioncontrasting
confidence: 90%
“…[33][34][35][36][37][38] The frequency of CYP2C19*17 allele found in the present study (MM from Central Mexico) shows a minor nonsignificant difference from that found in a recent report in MM from the state of Jalisco (0.09 and 0.14, respectively). 38 The frequency of ABCB1 3435C4T in the MM population studied here is similar to that found in previous reports. 39,40 Also comparable with our results were the frequencies of the three ABCB1 polymorphisms reported among individuals with Mexican ancestry living in Los Angeles, California (ABCB1 1236C = 0.540, 2677G = 0.570 and 3435C = 0.540; data from HapMap project consulted in NCBI dbSNP).…”
Section: Discussioncontrasting
confidence: 90%
“…Among the studied SNPs, only CYP3A4*1B, CYP2C19*2 and CYP2C19* 17 were polymorphic and in agreement with Hardy‐Weinberg expectations; the remaining SNPs were monomorphic (Table ). Comparison with other populations demonstrated homogeneity throughout Latin America for CYP2C19 (data not shown), as previously indicated . The estimated distribution for CYP3A4*1B was similar to Mexican, Tepehuano (Mexican indigenous), Caucasian and Spanish American populations (data not shown; P > .05) .…”
Section: Resultssupporting
confidence: 81%
“…Comparison with other populations demonstrated homogeneity throughout Latin America for CYP2C19 (data not shown), as previously indicated. 21 The estimated distribution for CYP3A4*1B was similar to Mexican, Tepehuano (Mexican indigenous), Caucasian and Spanish American populations (data not shown; P > .05). [9][10][11][12][13] Conversely, it was different from Colombian, Central American and one Caucasian population (data not shown; P < .05).…”
Section: Cyp2c19 and Cyp3a4 Genotypesmentioning
confidence: 61%
“…Recent data demonstrate significant alteration in the enzyme activity result in variable drug responses and increased rates of thrombotic events in patients harboring hepatic cytochrome gene variants [ 10 , 17 19 ]. CYP2C19*2 and CYP2C19*3 alleles, which result in the aberrant splicing and a premature stop codon, respectively, have been extensively studied in populations of different ethnicities and geographic origin [ 20 23 ]. Since CYP2C19*2 and *3 cover >90% of the poor metabolism population, the mutation genotype contained *1/*2, *1/*3, *2/*2, *2/*3, and *3/*3.…”
Section: Discussionmentioning
confidence: 99%